The participation of PO, DENR, and LGU in the community-based forest management program towards sustainable forest management in Maasin, Iloilo - Padilla, Agnes L (2004.)
This study aims to determine the role, functions and level of participation of PO, DENR, AND LGU in Community Based Forest Management Program Towards Sustainable Forest Management., The study was conducted in the Municipality of Maasin particularly where the CBForm Program was implemented. There were 28 purposively chosen respondents in the study. Six were from DENR, 19 from the PO, and 4 from the LGU. They were given questionnaires that would assess their particiaption in the program and questionnaires that would assess the participation of the other two actors. Their participation was assessed based on their performance of their roles and functions as stipulated in the program. Further, criteria were set in quantifying their participation. For PO, the criteria were participation in the implementation of the program, participation in terms of legal compliance, and participation in terms of rendering support to the organization. For the DENR, the criteria included participation in the implementation of the program, participation in terms of rendering support to the PO, and participation in terms of monitoring and evaluation. And for the LGU, the criteria were particiaption in terms of rendering support for the program, particiaption in the monitoring and evaluation, and participation in terms of establishing linkages with other institutions.
Research Project (Undergraduate, Bachelor of Arts in Political Science-Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Forest Management Program Towards Sustainable Forest Management -- Maasin, Iloilo